ГОСУДАРСТВЕННЫЙ КОНТРОЛЬ В РЕСПУБЛИКЕ КАЗАХСТАН: КОНСТИТУЦИОННО-ПРАВОВЫЕ ПРОБЛЕМЫ - Taytorina, B.A. (Journal of actual problems of jurisprudence, 2019)
In article are considered problems of maintenance of the state control in the light of the Concept of a legal policy of Republic Kazakhstan for the period with 2010 till 2020. On the basis of the analysis of concept and kinds of the state control pressing questions of perfection of the given statelegal institute are considered.